Introduction to administrative law - Cane, Peter (New York, 1996)
This is the third edition of Peter Cane's popular and accessible introduction to administrative law. Like the previous editions, it has two main aims; to provide a clear and concise statement of the law concerning judicial control of governmental administrative action, and to provide a wider framework for understanding the law. This edition has been extensively revised and updated to take into account important developments in administrative law during the past four years including, for example, changes in the areas of standing, freedom of information, and tort liability. The underlying theme of the book is that the role of the courts in adjudicating complaints against government is not that of neutral arbiter but rather that of active participant in the public decision-making process.
Keywords: Administrative law